Evaluation of the relation between the pulp stones and direct restorations using cone beam computed tomography in a Turkish subpopulation - Güzide Pelin Sezgin; Sema Sönmez Kaplan; Tuna Kaplan (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to assess the presence of pulp stones through an examination of cone beam computed tomography images and correlate their prevalence with age, sex, dental arch and side, tooth type, and restoration type and depth.Materials and MethodsCone beam computed tomography images obtained from 673 patients and archival data on 11,494 teeth were evaluated. The associations of pulp stones with age, sex, dental arch and side, tooth type, and restoration type and depth were noted. All the measurements were subjected to a χ2 test and one sample χ2 test (p < 0.05).ResultsIn the study group, 163 (24.2%) patients and 379 (3.3%) teeth had at least one pulp stone. The pulp stone frequency in those aged 30–39 years was significantly greater than in those aged 18–29 and ≥ 60 years, and the frequency was higher in females than in males (p < 0.05). The highest prevalence of pulp stones was found in maxillary dental arches and molar teeth (p < 0.05). Pulp stones were significantly more common in medium-depth restorations (p < 0.05).ConclusionsMaxillary molar teeth, medium-depth restorations, individuals aged 30–39 years and females had a greater percentage of pulp stones.